Production of liquid compounds by co-pyrolysis of different pre-treated biomasses mixed with plastic wastes - Pinto, Filomena (2020)
ABSTRACT: As an innovation to conventional biomass pyrolysis to produce liquid biofuels, different types of biomass wastes were pre-treated by autohydrolysis, prior to pyrolysis. Eucalyptus forestry waste, corn cobs agricultural residue, and miscanthus (an energy crop) were autohydrolysed. Autohydrolysis led to valuable sugar-rich stream that may be used in fermentation and to solids rich in lignin that were pyrolysed. Pyrolysis of autohydrolysed eucalyptus led to an increase in liquids yields of 24 % in relation to untreated eucalyptus, as autohydrolysis weakened initial macromolecular structure and thus helped chemical bonds breakdown during pyrolysis. However, similar pyrolysis liquid yields were obtained by autohydrolysed or untreated corn cobs and miscanthus, thus feedstock composition is an important issue. Nevertheless, the production of added value products by autohydrolysis may still justify this pre-treatment. Otherwise, more severe pre-treatments of these biomasses might improve co-pyrolysis as it happened with eucalyptus. As polyethylene (PE) is easier to pyrolyse than biomass and greatly favours the production of liquid hydrocarbons, autohydrolysed and untreated biomass was mixed with PE wastes to be used in co-pyrolysis. The rise of PE content in the blend clearly favoured the production of liquid products of pre-treated and untreated biomass. 75 %wt. of PE in the blend led to liquid yields of 72 %wt. for untreated eucalyptus and of 82 %wt. for autohydrolysed eucalyptus.